Is Publishing Country-of-Design Information Beneficial for MNCs?. Issue 5 (20th October 2017) - Genç, Ebru; Wang, Shih-Ching
ABSTRACT: In this study, we examined the effect of a countering strategy of manipulating country-of-manufacturing (COM) with country-of-design (COD) information that has been adopted by multinational corporations (MNCs). We conducted a (2 (COM: China vs. Italy) *3 (COD: China vs. Italy vs. None) * 2 (Consumption Context: Public use vs. Private use) mixed factorial design to test the interaction effect of COM and COD in varying levels of country development and in different consumption contexts . We found that, counter-intuitively, it is not advantageous to signify design location at developed countries if manufacturing in developing countries. Contrarily, emphasizing design location at developed countries has a reinforcing positive effect for firms manufacturing at developed countries as well. Second, compared to products typically used in private, COM has significantly higher impact on product evaluation and purchase intention for products used in public. However, our results showed no interaction effect between consumption context and COD.